Penerapan Permainan Edukatif Teka Teki Silang Dalam Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Zakiah Ulfiah; Yona Wahyuningsih (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
The low motivation to learn in students is due to the lack of innovation in teachers in providing teaching to students. Lack of innovation in learning indicates a low quality of education. Teachers who apply one-way learning too often cause students to become passive and not interested in participating in learning so that students do not focus on participating in learning. Therefore, teachers need learning innovations that involve active teachers and students during the learning process. One of the lessons that involves the activities of teachers and students in the learning process is crossword puzzles (TTS). The purpose of this research is to know what application game educational crossword puzzles (TTS) can increase motivation to learn in students. The research method used is descriptive qualitative. The application of crossword puzzle games (TTS) results in changes in student behavior to become more enthusiastic about participating in a series of learning activities. Students become more active during the learning process going on. This shows that the application of crossword puzzles (TTS) can increase learning motivation in elementary school students